Problematika Guru dalam Menerapkan Pembelajaran Tematik Kurikulum 2013 di Kelas VI SDN Peninggilan 5 - Tiara Martha Aisyah; Hindun Hindun (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
This research uses a qualitative descriptive approach by utilizing observation, interviews and documentation analysis to determine the difficulties faced by teachers in implementing thematic learning. Research participants included the principal and class VI teachers at SD Negeri Peninggilan 5. The research findings revealed several main difficulties faced by teachers. First, at the planning stage, teachers have difficulty integrating lesson material into classroom learning steps when preparing lesson plans. Second, during implementation, teachers consider thematic learning to be time consuming because it covers many subjects and remains teacher-centered. Finally, in terms of evaluation, teachers experience difficulties in assessing students' affective mood due to individual differences, as well as facing challenges in completing subject-specific student learning outcomes reports. Efforts to overcome these difficulties so that thematic learning can be useful in improving the overall quality of teaching for other teachers.